The Economic Profitability of Photovoltaic Installations in Blida 2 University in Algeria - Cherif AMROUCHE; Merouane MEHDI; Samia NEZALI (Management and Economics Review)
Our society is increasingly faced with the problem of global warming. considering the sustainable development is the only possible alternative for tackling this problem, renewable energies are essential to initiate the energy transition. In this process, the university has a major role to play and has a duty to set an example. This article sets out the adoption of solar panels at Blida 2 University and its benefits economic, where we analyse the possibility of a photovoltaic project for BLIDA 2 university. We will start by conducting a review of the existing literature to pinpoint the factors that impact the acceptance of technologies, such as panels. Afterward, we will delve into the underpinnings of this technology. Next, we will conduct a study to determine if investing in panels is a choice, by examining the electricity usage a t the university. Finally, we will calculate the profitability of this solution, as well as the reduction in the carbon footprint on campus using the Retscreen simulation program, the results of the study concluded that adopting photovoltaic panels as an energy alternative at the University of Blida 2 will have a positive economic return in the long term.